Integration of Religious Knowledge with General Science to Face the Era of Globalization at the Hidayatul Mubtadi'ien Islamic Boarding School - Muhammad Najih; Amril M.; Evadewi (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
Religious knowledge and general knowledge are very important that every human being must have so that humans are lucky with the provision of general knowledge in the world and are able to face the challenges of zaaman in the era of globalization and also lucky with their religious knowledge in the hereafter. For the sake of a balance between religious science and general science, there needs to be a policy so that both are balanced. In this case, the researcher explores or examines more deeply the polemic issue among students about the integration of religious science and general science for students in facing the era of globalization at the Hidayatul Mubtadi'ien Sumber Makmur Islamic Boarding School. The concept of integrating religious knowledge and general knowledge can be seen in the latest innovation, namely by integrating two different things, between religious knowledge and general knowledge which is realized by learning English. For the application of the integration of religious science and general science by students in facing the era of globalization through additional.